2011
DOI: 10.1186/1471-2164-12-186
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of the skeletal muscle miRNA transcriptome of chicken varieties with divergent skeletal muscle growth identifies novel miRNAs and differentially expressed miRNAs

Abstract: BackgroundFunctional studies have demonstrated that microRNAs (miRNAs or miRs) play critical roles in a wide spectrum of biological processes including development and disease pathogenesis. To investigate the functional roles that miRNAs play during chicken skeletal muscle development, the miRNA transcriptomes of skeletal muscles from broiler and layer chickens were profiled using Solexa deep sequencing.ResultsSome miRNAs have multiple isoforms and several miRNAs* are present at higher levels than their corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
63
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 89 publications
(120 reference statements)
15
63
1
1
Order By: Relevance
“…Studies indicate that miR-130a is associated with lung cancer [50], gastric cancer [51,52], ovarian cancer [53][54][55][56][57], cervical cancer [58,59], and prostate cancer [60]. Recently, deep sequencing technology was used to identify differentially expressed host miRNAs in chickens [28,34,35,61,62]. Burnside et al reported that ggamiR-130a expression was lower in MDV-infected samples [28], a finding that is consistent with results from a previous study by our team [34].…”
Section: Discussionsupporting
confidence: 90%
“…Studies indicate that miR-130a is associated with lung cancer [50], gastric cancer [51,52], ovarian cancer [53][54][55][56][57], cervical cancer [58,59], and prostate cancer [60]. Recently, deep sequencing technology was used to identify differentially expressed host miRNAs in chickens [28,34,35,61,62]. Burnside et al reported that ggamiR-130a expression was lower in MDV-infected samples [28], a finding that is consistent with results from a previous study by our team [34].…”
Section: Discussionsupporting
confidence: 90%
“…3). Our data show similar results as reported previously: the miRNA expression patterns in broilers and layers were investigated in skeletal muscles, and let-7c, miR-15b, miR-15c, and miR-2188 were differentially expressed [15]. In addition, miR-133a, miR-181a, and miR-206 were also muscle specific in mouse, pig, beef cattle, and other species [11,24].…”
Section: Discussionsupporting
confidence: 78%
“…According to the homology of the species, we boldly speculate that these miRNAs are also involved in the skeletal muscle differentiation in broilers. Recently, numerous miRNAs have been discovered in various chicken organs and tissues, such as embryo, somite, pre-adipocyte, and skeletal muscle [12,13,14,15], but the miRNA expression profiles of the broiler skeletal muscle awaits further study.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same cloning strategy, Wang et al identified 47 miRNAs from chicken adipose tissue and skeletal muscle (Wang et al, 2012). Using deep sequencing, 123 miRNAs were discovered from embryonic chick livers at embryonic days 15 (E15) and E20 , 121 known chicken miRNAs, 449 new chicken miRNAs and 39 mirtrons were identified from E5, E7 and E9 chicken embryos (Glazov et al, 2008), and 63 and 33 novel chicken miRNAs were identified from chicken preadipocytes and skeletal muscle, respectively (Li et al, 2011c;Yao et al, 2011). Microarrays were used to profile the expression of chicken miRNAs at different stages of gonadal sex differentiation.…”
Section: Mirnas In Chickensmentioning
confidence: 99%
“…Li and colleagues further identified the activin receptor 2B (ACVR2B) gene as a miR-1 target in chicken muscle (Li et al, 2011c).…”
Section: Mirnas In Chickensmentioning
confidence: 99%